Bioinformatic analysis of endogenous and exogenous small RNAs on lipoproteins. Issue 1 (13th August 2018) - Allen, Ryan M.; Zhao, Shilin; Ramirez Solano, Marisol A.; Zhu, Wanying; Michell, Danielle L.; Wang, Yuhuan; Shyr, Yu; Sethupathy, Praveen; Linton, MacRae F.; Graf, Gregory A.; Sheng, Quanhu; Vickers, Kasey C.
ABSTRACT: To comprehensively study extracellular small RNAs (sRNA) by sequencing (sRNA‐seq), we developed a novel pipeline to overcome current limitations in analysis entitled, "Tools for Integrative Genome analysis of Extracellular sRNAs (TIGER)". To demonstrate the power of this tool, sRNA‐seq was performed on mouse lipoproteins, bile, urine and livers. A key advance for the TIGER pipeline is the ability to analyse both host and non‐host sRNAs at genomic, parent RNA and individual fragment levels. TIGER was able to identify approximately 60% of sRNAs on lipoproteins and >85% of sRNAs in liver, bile and urine, a significant advance compared to existing software. Moreover, TIGER facilitated the comparison of lipoprotein sRNA signatures to disparate sample types at each level using hierarchical clustering, correlations, beta‐dispersions, principal coordinate analysis and permutational multivariate analysis of variance. TIGER analysis was also used to quantify distinct features of exRNAs, including 5ʹ miRNA variants, 3ʹ miRNA non‐templated additions and parent RNA positional coverage. Results suggest that the majority of sRNAs on lipoproteins are non‐host sRNAs derived from bacterial sources in the microbiome and environment, specifically rRNA‐derived sRNAs from Proteobacteria. Collectively, TIGER facilitated novel discoveries of lipoprotein and biofluid sRNAs and has tremendous applicability for the field of extracellular RNA.